Evolution of fumarolic anhydrous copper sulfate minerals during successive hydration/dehydration. (2nd April 2021) - Siidra, Oleg I.; Borisov, Artem S.; Charkin, Dmitri O.; Depmeier, Wulf; Platonova, Natalia V.
Abstract: Hydration processes of primary anhydrous minerals as well as dehydration of the hydrated phases are relevant not only for answering geochemical and petrological questions, but are also interesting in the context of the theory of the 'Evolution of minerals'. Our study of the evolution of anhydrous exhalative sulfates in hydration and dehydration processes has demonstrated the complexity of the processes for a number of minerals from the active high-temperature fumaroles of Tolbachik volcano (chalcocyanite Cu(SO4 ), dolerophanite Cu2 O(SO4 ), alumoklyuchevskite K3 Cu3 AlO2 (SO4 )4 and itelmenite Na2 CuMg2 (SO4 )4 ). Hydration and dehydration experiments were carried out for all four minerals using powder X-ray diffraction. A typical structural characteristic of several anhydrous copper sulfate minerals of fumarolic origin is the presence of oxygen-centred OCu4 tetrahedra. These are absent in the structures of all known hydrated minerals or synthetic compounds of the class under consideration. Hydration of minerals initially containing O 2– anions as part of oxocomplexes, proceeds with sequential formation of a large series of hydroxysalts. On the contrary, hydration of itelmenite with its relatively complex 'initial' structure, but without additional oxygen atoms that are strong Lewis bases, results in formation of simpler hydrates. The lower the temperature and the larger the excess of water, the stronger the tendency of the cations to adopt higher hydration numbers thus outcompeting the sulfate anions as ligands. Ultimately, the water molecules completely expel the bridging sulfate anions from the metal coordination sphere yielding relatively simple fully hydrated structures.